The importance of futsal practice in the frequency and motivation of the students of the one special school (Research, Society and Development, 2020)
Many parents of students with disabilities place their children in specialized schools in order to improve the teaching-learning processes. However, the frequency and motivation of students at school involve different factors. Considering that body practices can be one of the factors that motivate students and improve their attendance at school, this proposal aimed to investigate this issue. The general objective of the study was to analyze the participation of students from a special school in different educational activities, from the experience of the Futsal Project. The research methodology presented the qualitative and quantitative approach. The research context was a Special School located in a municipality in the State of Rio Grande do Sul. The research subjects were all professionals directly involved in the care of students with disabilities at school: nine (9) class teachers, three (3) professionals from the technical team (two psychologists and a social worker), three (3) professionals from the management team (two pedagogical coordinators and one director), 60 students and 60 parents from the Special School Futsal project. Data collection was performed using a closed and open questionnaire (mixed). The results showed that the Futsal Project is of great relevance to the frequency of students at this school, proving that on Futsal training days the frequency is above the regular average. In addition, this activity keeps them motivated in the school environment, by inserting themselves in other sports, sports, musical and artistic projects, improving their relationship at school, being also important in socializing.